Maintaining a balance of religious freedom and animal rights - Mukasheva А.А.; Ibrayev А.С.; Bolatbekova И.К. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2023)
This article explores how kosher and halal slaughter without prior stunning causes unnecessary suffering to animals and attempts to find a balance between animal welfare and religious freedom. The connection between religion and animal slaughter is related to religious prescriptions and requirements that may affect the method and conditions of slaughter. In various religions, there are certain rules and rituals related to the killing of animals for food, including requirements for anesthesia, slaughter methods and prayer rituals. For example, in Islam there are requirements for halal slaughter, which is carried out in accordance with the principles of Islamic law. This includes the use of sharp knives, a single cut of the animal’s throat, mandatory anesthesia and reciting prayers during slaughter. Other religions and cultures may also have their own specific requirements and rituals related to the slaughter of animals. It is important to note that the connection between religion and animal slaughter allows believers to perform rituals in accordance with their religious beliefs and principles. At the same time, many countries have legislative acts and regulatory requirements that regulate and control the process of slaughtering animals, taking into account religious and regime features.